Five Active Components Compatibility of Astragali Radix and Angelicae Sinensis Radix Protect Hematopoietic Function Against Cyclophosphamide-Induced Injury in Mice and t-BHP-Induced Injury in HSCs - Wei Zhang; Jia-huan Zhu; Hao Xu; Xiao-Ping Huang; Xiao-Dan Liu; Chang-Qing Deng (Frontiers Media S.A., 2019)
Although the compatibility of Astragali Radix (AR) and Angelicae Sinensis Radix (ASR) has favorable effect on promoting hematopoiesis in traditional Chinese medicine (TCM), the main active components and pharmacological mechanism are unknown. We investigated the five active components and its mechanisms in vitro and in vivo. Five active components of Astragalus glycosides (AST), Formononetin (FRM), Ferulic acid (FRA), Calycosin (CAL), and Calycosin-7-glucoside (CLG), which could be absorbed in intestinal tract, were detected in this study. The peripheral blood, hematopoietic growth factors (HGFs), and hematopoietic progenitor cells (HPCs) colony were observed to evaluate the effect of these five active components promoting hematopoiesis. Furthermore, hematopoietic stem cell (HSC) proliferation, aging, cycle, and related proteins were detected to explore the mechanism of these five components promoting HSC proliferation. i) The in vivo experiments showed that the combination of the five active components could remarkably increase the number of RBCs, WBCs, PLTs, and content of Hb in peripheral blood and the area of bone marrow hematopoietic tissue, as well as thrombopoietin (TPO), erythropoietin (EPO), granulocyte-macrophage colony stimulating factor (GM-CSF), and colony of CFU-GM, CFU-MK, CFU-E, and BFU-E in serum. Each of these five components promoted the recovery of RBCs and Hb, and increased TPO, CFU-MK, and CFU-E. All components except for AST increased the CFU-GM. FRA increased the number of WBCs, the area of bone marrow hematopoietic tissue, and BFU-E. FRA and AST promoted PLT recovery. FRA and CAL improved the content of GM-CSF. FRA, CAL, and CLG improved the content of EPO. ii) The in vitro experiments showed that FRA, FRM, and AST significantly promoted cell proliferation, reduced the positive rate and G0/G1 cells, and increased G2/M + S cells and the expression of cyclin D1 and CDK4 proteins in aging HSCs. Furthermore, the combination of five components had the best effect. Taken together, the five active components of AST, FRM, FRA, CAL, and CLG were the main pharmacodynamic substances of the AR-ASR compatibility, which promoted hematopoiesis. The combination of them had a synergistic effect. The mechanism of promoting hematopoiesis may be relevant to regulating cyclin-related proteins, promoting cell cycle transformation, and promoting HSC proliferation.